Physical Activity Patterns and Risk of Type 2 Diabetes and Metabolic Syndrome in Middle-Aged and Elderly Northern Chinese Adults - Qian Wang; Xu Zhang; Li Fang; Qingbo Guan; Ling Gao; Qiu Li (Journal of Diabetes Research)
The main aim of this study is to quantitatively describe the status of physical activity and evaluate its levels in a rural population and to investigate the association between the quantifiable physical activity and type 2 diabetes and metabolic syndrome. In total, 2076 participants aged over 40 years were included in a cross-sectional analysis. Physical activity status and the contributions of different types of activity were evaluated. The association between social behaviors and physical activities was analyzed. In addition, the impact of physical activities on type 2 diabetes mellitus and metabolic syndrome was also analyzed by logistic regression. Approximately half of the total activity in rural areas consisted of work-related activity (49.3%) followed by commuting (30.2%) and recreational activity (20.5%). In rural areas, the prevalence of physical activity levels was 28.6% for low levels, 47.3% for moderate levels, and 24.1% for high levels. Educational level showed a significant negative association with the physical activity level. Lower physical activity shows a strong and significant association with type 2 diabetes and metabolic syndrome. In conclusion, insufficient physical activity among rural people over 40 years old increases the risk of type 2 diabetes and metabolic syndrome. Population-wide and individualized guidelines for physical activities especially recreational physical activities should be developed.